Многофакторная модель, как метод определения направления инвестирования на промышленном предприятии - Кучина, Светлана Эдуардовна; Ларка, Николай Иванович (Харківський національний економічний університет ім. Семена Кузнеця, 2006)
В статье обосновано и рассмотрено на примере применение многофакторной модели для определения приоритетности вложения средств в развитие бизнес-единицы.

The necessity of introduction of multifactor model is considered, determinations of direction of investment of facilities, for the improvement of quality of business-unit on an industrial enterprise. The offered algorithm of construction of this model enables to take into account different technical-economical indexes for realization of strategic development of business-units of enterprise.
Multifactor model is considered, determination of direction of investment an industrial enterprise
Keywords: матрица БКГ; бизнес-единица; технико-экономические параметры; блок-схема; конкуренция; рынок